The predictive value of SOFA and APSIII scores for 28-day mortality risk in SIMI: a cohort study based on the MIMIC-IV database - Chang Liu; Hao Wang; Chenyang Liu; Min Cao (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThe objective of this study was to systematically identify and evaluate scoring systems that predict the prognosis of patients with sepsis-induced myocardial injury (SIMI).MethodsData were retrieved from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Logistic and Cox regression analyses were conducted to identify risk factors associated with 28-day mortality in patients with sepsis-induced myocardial injury (SIMI). The prognostic performance of the scoring systems was comprehensively assessed using receiver operating characteristic (ROC) curves, Kaplan-Meier survival and decision curve analysis (DCA).ResultsLogistic regression analysis showed that Acute Physiology Score III (APSIII) (Odds Ratio [OR] =1.011, 95% Confidence Interval [CI] 1.002–1.018, P=0.005), Sequential Organ Failure Assessment (SOFA) (OR =1.097, 95% CI 1.045–1.144, P<0.001), and Charlson Comorbidity Index (CHARLSON) (OR=1.095, 95% CI 1.048–1.145, P=0.036) were independent risk factors for 28-day mortality in SIMI patients. Cox regression analysis confirmed that SOFA (HR=1.082, 95% CI 1.054– 1.111, P<0.001), APSIII (HR=1.010, 95% CI 1.005–1.015, P<0.001), and CHARLSON (HR=1.044, 95% CI 1.012–1.077, P=0.007) were independent risk factors. ROC curve analysis showed that SOFA (AUC=0.685, 95% CI 0.663–0.707) and APSIII (AUC=0.683, 95% CI 0.662–0.705) had significantly higher AUC values compared to other scoring systems. DCA results showed that APSIII and SOFA had better net benefit than other scoring systems.ConclusionsThe SOFA and APSIII scores effectively identified high-risk patients with SIMI, providing evidence-based support for early clinical intervention.